2017
DOI: 10.1534/genetics.116.195784
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analyses of Selection Operating on Nontranslated Intergenic Regions of Diverse Bacterial Species

Abstract: Nontranslated intergenic regions (IGRs) compose 10-15% of bacterial genomes, and contain many regulatory elements with key functions. Despite this, there are few systematic studies on the strength and direction of selection operating on IGRs in bacteria using whole-genome sequence data sets. Here we exploit representative whole-genome data sets from six diverse bacterial species: ,, ,, , and We compare patterns of selection operating on IGRs using two independent methods: the proportion of singleton mutations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 59 publications
5
72
0
Order By: Relevance
“…Selection has historically been thought to act largely on amino acid changes in coding sequences; however, recently it has been shown that IGRs, which account for ~15% of microbial genomes, may also be acted upon by selection (Thorpe et al, 2017). Further, parallel evolution has also been observed among longitudinal intrahost samples of P. aeruginosa from CF infection (Khademi and Jelsbak, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Selection has historically been thought to act largely on amino acid changes in coding sequences; however, recently it has been shown that IGRs, which account for ~15% of microbial genomes, may also be acted upon by selection (Thorpe et al, 2017). Further, parallel evolution has also been observed among longitudinal intrahost samples of P. aeruginosa from CF infection (Khademi and Jelsbak, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This implies, from the rate at which non-synonymous mutations accumulate relative to synonymous mutations, that δ n = 0.6. A recent analysis of intergenic regions in several species of bacteria has concluded that selection is weaker in intergenic regions than at non-synonymous sites, we therefore assume that δ i = 0.8 (30). Using these estimates suggests that selection leads us to an underestimate of the true mutation rate per year in the wild by ~27%; this in turn means we have underestimated the DT by ~27%, a relatively small effect.…”
Section: Discussionmentioning
confidence: 99%
“…Due to computational limitations (BEAST analyses), we necessarily took measures to limit our data set to <600 isolates. For countries with large numbers of available genomes, we implemented a subsampling strategy similar one previously described (Thorpe, Bayliss, Hurst, & Feil, ), whereby phylogenetic lineage diversity was captured thus minimizing the overrepresentation of clonal complexes (e.g., outbreaks): phylogenetic inference on all isolates available from a country was performed with Fasttree (Price, Dehal, & Arkin, ) and a random isolate was selected from each clade extending from n branches, where n was the desired number of isolates from the country. Numbers of isolates per country were selected based on the availability of appropriate genome sequence data as well as TB prevalence (Figure ) (World Health Organization, ).…”
Section: Methodsmentioning
confidence: 99%